TINDAK PIDANA NARKOBA DALAM PERSPEKTIF HUKUM POSITIF INDONESIA (STUDI KASUS PENYELUNDUPAN NARKOBA KE LAPAS NUSAKAMBANGAN) - Yusuf Setyadi; Wahyu Wibowo (JOURNAL OF LAW AND NATION, 2022)
Talking about narcotics crimes, we are always faced with the existing reality, where crimes are committed individually to involve certain groups in a community from the lower class to the upper middle class society and even to involve law enforcement officers. Drug smuggling and distribution is not only around the community, but also even in prisons and detention centers. For example, in 2012, seven Nusakambangan prisoners were proven to be the masterminds of the distribution of 3.9 kilograms of narcotics, and several other cases. This study aims to analyze the causes and prevention of narcotics crimes based on Indonesian positive law. This research method is a normative method that is useful for finding and formulating legal arguments through analysis of the subject matter. As a result, the lack of control or supervision from prison officers over drug trafficking in prisons or detention centers causes an increase in drug trafficking. Therefore, the prevention and control of narcotics abuse must be pursued as much as possible from various parties.